Treatment of contact lens related dry eye with intense pulsed light. Issue 2 (April 2022) - Yang, Lanting; Pazo, Emmanuel Eric; Zhang, Qing; Wu, Yi; Song, Yilin; Qin, Guanghao; Zhang, Hongda; Li, Jun; Xu, Ling; He, Wei
Abstract: Aim: The prevalence of contact lens related dry eye (CLDE) is high and can lead to ocular discomfort, reduced quality of vision and life. The aim of this study was to assess the efficacy of intense pulsed light (IPL) treatment in alleviating signs and symptoms of CLDE. Design: Prospective, randomised, examiner masked study. Methods: This prospective study was conducted on 152 eyes of 76 patients (IPL group, n = 76 eyes; control group, n = 76 eyes) wearing contact lens (CL) and experiencing CLDE for more than 1 year. The IPL treatment group underwent two IPL treatment sessions at 3-week intervals while the control group received sham IPL treatment. Best-corrected visual acuity (BCVA), ocular surface disease index (OSDI), non-invasive breakup time (NITBUT), tear film lipid layer (TFLL) quality, fluorescein staining (FS), meibum gland (MG) quality and expression, endothelial cell count (ECC) and intraocular pressure (IOP) were assessed at baseline (D-0), day-21 (D-21) and day-42 (D-42) after IPL treatment. Results: The mean age of treatment group and control group was 28.47 ± 5.16 years (21 females, 28 %) and 28.58 ± 4.33 years (23 females, 30 %) respectively. IPL treatment group had clinically and statistically significant improvement in mean NITBUT was observed at D14 (5.24 s, P< 0.001) and D28 (6.08 s, P< 0.001). OSDI, TFLL score and MG quality and expressibility all improved significantly ( P< 0.001) at D-42, whereas BCVA, ECC and IOP showed no significant changes at D-21 and D-42 in IPL treatment group. The control group showed no significant improvement in all parameters at D-21 and D-42. Conclusion: Our findings suggest that CL related DE can be safely alleviated with IPL treatment as it reduced the severity of symptoms, improved the overall tear film stability and reduced artificial tear use in participants with CLDE.